Implementation of Insect Pest Control Innovation with Raindrop Sensor using Solar Energy Source in Shallots Farming - Prasojo, Rahman Azis; Fahad, Waris Malik; Nadila, Dilavinsa Indar Putri; Duanaputri, Rohmanita; Hakim, Muhammad Fahmi; Sungkowo, Heri; Handani, Galuh Prawestri Citra (Institut Teknologi Nasional, Bandung, 2024)
Spodoptera exigua, commonly known as the beet armyworm, is a major pest affecting shallot (Allium ascalonicum L.) plants, leading to significant damage and economic losses for farmers. Traditional pest control methods, such as manual caterpillar removal and pesticide application, have proven ineffective and costly. In response, this study aims to develop an environmentally friendly and sustainable solution by designing a pest control system powered by solar energy, equipped with high-voltage wires, UV lamps, and a raindrop sensor for automatic operation. The system works by converting solar energy into electrical power, which then supplies the pest control unit. The UV lamps attract moths, while the high-voltage wire eliminates them. A raindrop sensor is used to ensure the system operates efficiently by shutting off during rainfall. The method involved discussions with local farmers, design and assembly of the device, followed by field implementation and monitoring in shallot farms. The results show that the device successfully trapped between 40 to 80 moths per day, significantly reducing pest populations and lowering production costs for farmers, as the use of chemical pesticides was minimized. Additionally, the quality of shallot crops improved, leading to higher market value. The solar-powered pest control system is an effective, eco-friendly alternative for managing pest infestations in shallot farming. It offers a cost-efficient solution, reducing the need for pesticides while improving crop quality and yield.